New Therapeutic Strategies in Retinal Vascular Diseases: A Lipid Target, Phosphatidylserine, and Annexin A5-A Future Theranostic Pairing in Ophthalmology - Anna Frostegård; Anders Haegerstrand (MDPI AG, 2024)
Despite progress in the management of patients with retinal vascular and degenerative diseases, there is still an unmet clinical need for safe and effective therapeutic options with novel mechanisms of action. Recent mechanistic insights into the pathogenesis of retinal diseases with a prominent vascular component, such as retinal vein occlusion (RVO), diabetic retinopathy (DR) and wet age-related macular degeneration (AMD), may open up new treatment paradigms that reach beyond the inhibition of vascular endothelial growth factor (VEGF). Phosphatidylserine (PS) is a novel lipid target that is linked to the pathophysiology of several human diseases, including retinal diseases. PS acts upstream of VEGF and complement signaling pathways. Annexin A5 is a protein that targets PS and inhibits PS signaling. This review explores the current understanding of the potential roles of PS as a target and Annexin A5 as a therapeutic. The clinical development status of Annexin A5 as a therapeutic and the potential utility of PS-Annexin A5 as a theranostic pairing in retinal vascular conditions in particular is described.